A journey of gender in health: Transforming health by promoting gender considerations through comic art. (1st July 2021) - Joy, Phillip; Cosma, Alina; Goodliffe, Samantha; Hiltner, Sarah; Magnée, Tessa; Plug, Ilona
Sex and gender are determinants of health outcomes across an individual's life course. However, often in health research and practice, sex and gender considerations are either overlooked or confounded. Recent developments in health research and practice ask for the inclusion of sex and gender considerations within health research and practice. This article is a reaction to these calls. It explores the ways in which an international team of health researchers created a comic book that highlighted the impact of gender in many areas of health across an individual's life course. The creative processes are critically explored, as well as selected images. Through this work, it is proposed that comic art knowledge mobilization projects can be viewed as means to transform health research and practice by critiquing and disrupting dominant cis-heteronormative sex and gender discourses.